Progression of small vessel disease correlates with cortical thinning in Parkinson's disease. (October 2016) - Foo, Heidi; Mak, Elijah; Yong, Ting Ting; Wen, Ming-Ching; Chander, Russell Jude; Au, Wing Lok; Tan, Louis; Kandiah, Nagaendran
Abstract: Objective: Cerebral small-vessel disease (SVD) is a risk factor for dementia in Parkinson's disease (PD), however the pathophysiological role of SVD in PD-dementia is unclear. We investigated the impact of baseline and progression of SVD on cortical thickness and the correlation to cognition. Methods: Seventy-three mild PD patients with baseline and follow-up structural MRI scans, serial clinical and neuropsychological assessments were studied. SVD included the load of white matter hyperintensities (WMH), lacunes and perivascular spaces (PVS). WMH progression was assessed using the modified Rotterdam Progression scale, while for lacunes and PVS, development of new lesions was considered as lesion progression. Patients were classified as having SVD-progression and SVD-no-progression based on the longitudinal changes in their SVD measures. Freesurfer was used to measure baseline and follow-up regional cortical thickness and subcortical volumes and correlated to cognitive performance. Results: Fourteen patients were classified as SVD-progression and 59 as SVD-no-progression. Over 18 months, PD SVD-progression demonstrated significant cortical thinning in the left frontal and bilateral parietal regions with associated decline in memory, executive function, and motor functions. PD SVD-progression also had reduced volumes in the nucleus accumbens and amygdala at baseline and greater atrophy in the caudate nucleus over 18 months. Discussion: The extent and progression of SVD is associated with focal cerebral atrophy and domain-specific cognitive dysfunction. Measures to retard SVD may be potentially useful in preventing dementia in PD. Highlights: Progression of small vessels disease (SVD) in Parkinson's disease (PD) was studied. Cortical thinning in frontal-parietal cortices was found in PD SVD-progression. This was associated with decline in memory, executive, and motor functions. Caudate nucleus was also implicated in PD SVD-progression. SVD-progression could accelerate focal cerebral atrophy with resultant dysfunction.